Penerapan Metode Rough Set Untuk Persediaan Obat-Obatan Di RSUP Haji Adam Malik Medan - Tifanny Anggraini; Melda Panjaitan (JURIKOM (Jurnal Riset Komputer), 2018)
Apotek RSUP H.Adam Malik is a distributor pharmacy for drug depots and cosmetics stores. Apotek RSUP H.Adam Malik still has a manual system in calculating the stock of medicines. Then the drug stock data is stored in Microsof Excel. To find out the amount of stock of drugs takes a long time because there is no picture of how much stock of drugs that exist (remaining) to avoid the occurrence of stock void. Supervision conducted on stocking of drug stocks. During this time only by monitoring the remaining drugs. The problem that happened in Apotek RSUP H.Adam Malik was not able to predict the stock of medicine for next year. In this final project, a system of drug stock prediction is made, which is information system designed to predict drug stock by using Rough Set method in pharmacy of H.Adam Malik MEDAN, to determine drug stock prediction. After this roughtset method is implemented this system can predict stock medicine at pharmacies RSUP.H.Adam Malik. From this application can be known picture prediction of drug stocks in the coming year and the results can be displayed in the form of reports, making it easier in analyzing and taking policy on drug stock.